Impact of protozoan cell death on parasite-host interactions and pathogenesis - Gonzalez-Rey Elena; Campos-Salinas Jenny; Lüder Carsten GK; van Zandbergen Ger (Parasites & Vectors, 2010)
Abstract PCD in protozoan parasites has emerged as a fascinating field of parasite biology. This not only relates to the underlying mechanisms and their evolutionary implications but also to the impact on the parasite-host interactions within mammalian hosts and arthropod vectors. During recent years, common functions of apoptosis and autophagy in protozoa and during parasitic infections have emerged. Here, we review how distinct cell death pathways in Trypanosoma, Leishmania, Plasmodium or Toxoplasma may contribute to regulation of parasite cell densities in vectors and mammalian hosts, to differentiation of parasites, to stress responses, and to modulation of the host immunity. The examples provided indicate crucial roles of PCD in parasite biology. The existence of PCD pathways in these organisms and the identification as being critical for parasite biology and parasite-host interactions could serve as a basis for developing new anti-parasitic drugs that take advantage of these pathways.